Development of recommendations for Ukrainian farming crediting based on the experience of other countries - Ivanyshyn, Volodymyr; Poprozman, Nataliia V; Haibura, Yuliia; Niskhodovska, Elena; Белей (Belei), Cвітлана (Svitlana) (Поліський національний університет, 2024)
The study aimed to address the farmers financing practices in Poland, France, Germany and Romania and to develop recommendations for reducing credit constraints in Ukrainian agriculture. Providing farms with financial resources is one of the most critical tasks for maintaining national resilience and stability in difficult times of military resistance. The study analysed statistical and economic indicators, the structure of farms and land use, financial instruments, features of financial institutions, practices and experience in lending in Poland, France, Germany, Romania and Ukraine. The impact of gross fixed capital formation on the volume of farm sales in comparable countries was addressed. The main reasons for the shortage of financing for medium, small, and micro-enterprises in the agro-industrial sector and numerous households that run private farms without establishing a legal entity were identified. The study noted that the main consequences of limited access to credit are low efficiency of land use, a decrease in gross domestic product and a deterioration in the viability of farms. The study analysed the impact of the state programme «Affordable Loans 5–7–9%» and other programmes to support medium, small and micro enterprises created with the help of international partners on the financial support of agricultural businesses. In recent years, these new financial instruments have significantly increased access to loans for farmers. The study addressed proposals of economic scientists of these countries on the elimination of credit restrictions in the activity of small agricultural producers. The analysis highlights the problems of farmers' lending that are common to all countries, as well as the many years of experience that have gradually resolved these issues. Recommendations on the implementation of the necessary measures for the timely receipt of affordable credit resources by small rural enterprises and family farms in Ukraine have been developed.
Development of recommendations for Ukrainian farming crediting based on the experience of other countries
Розробка рекомендацій з вирішення проблем кредитування фермерів України на основі досвіду інших країн
Keywords: agricultural support; investment; limited resources; agricultural sector; small and micro enterprises; financial instruments